2013
DOI: 10.1021/ja4029507
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Peptide Cyclodehydrations Achieved through the Chemoenzymatic Generation of Amide Derivatives

Abstract: Current strategies for generating peptides and proteins bearing amide carbonyl derivatives rely on solid-phase peptide synthesis for amide functionalization. Although such strategies have been successfully implemented, technical limitations restrict both the length and sequence of the synthetic fragments. Herein we report the repurposing of a thiazole/oxazole-modified microcin (TOMM) cyclodehydratase to site-specifically install amide backbone labels onto diverse peptide substrates, a method we refer to as azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 49 publications
5
79
0
Order By: Relevance
“…11,2427 The decrease in processing efficiency can often be rescued in part by the addition of the leader peptide in trans . These studies have demonstrated that, in addition to providing substrate recognition, leader peptides activate their cognate biosynthetic machineries, presumably by biasing the enzymes to an active conformation.…”
Section: Resultsmentioning
confidence: 99%
“…11,2427 The decrease in processing efficiency can often be rescued in part by the addition of the leader peptide in trans . These studies have demonstrated that, in addition to providing substrate recognition, leader peptides activate their cognate biosynthetic machineries, presumably by biasing the enzymes to an active conformation.…”
Section: Resultsmentioning
confidence: 99%
“…548 The hydrolytic susceptibility of thiazolines has been exploited to introduce [ 18 O] labels into peptides for mechanistic studies (AMPL method). 183 Ring opening of thiazolines in peptides with acidic [ 18 O]-H 2 O results in the incorporation of [ 18 O] at the preceding carbonyl oxygen position (Figure 34). In contrast, thiazoles cannot be hydrolyzed by simple acid or base treatment.…”
Section: Characterization Of Ripp Cyclodehydratasesmentioning
confidence: 99%
“…YcaO domains utilize ATP directly for catalysis (section 6.2.1) 17, 183 and it has been observed that these enzymes evolved to limit the non-productive hydrolysis of ATP. For example, ATP consumption is stoichiometric (1:1) with heterocycle formation so ATP is efficiently coupled to catalysis.…”
Section: Characterization Of Ripp Cyclodehydratasesmentioning
confidence: 99%
“…YcaO domain proteins activate backbone amide bonds by phosphorylation26, 27 or adenylation28 of the carbonyl oxygen, and all YcaO domain proteins with a characterized activity have a partner cyclodehydratase that aids catalysis of cyclization to oxazolines or thiazolines 29. The bottromycin gene cluster encodes two YcaO domain proteins, BtmE and BtmF, but no cyclodehydratases.…”
mentioning
confidence: 99%